Myths and realities: Voices of Japanese female graduate students. - Ako Tominaga (Adult Education Research Conference, 1997)
This ethnographic study identified sources of misperceptions about Japanese women and offered insight into the concept of Western feminism and the role it plays in these Japanese women's lives in a postmodern, cross-cultural context.